TEACHER INTERACTION FROM THE PERSPECTIVE OF HIGH SCHOOL STUDENTS: Received: 15th December 2023; Revised:12th February 2024, 27th February 2024; Accepted: 20th December 2023 - Szabó, László Dávid; Horváth , Kinga (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Based on Leary’s interpersonal model (Interpersonal Circumplex), Wubbels elaborated the scheme of interpersonal behavior that was completed by questionnaires (Questionnaire on Teacher Interaction (QTI)). Our research involved 110 high school students. The aim of our present research was to determine the teacher’s interaction style from the high school students’ perspective using the QTI measurement tool. The purpose of the research was to assess how students see the teacher’s classroom activities and how the teachers see themselves, and also to see whether there is a difference between the teacher’s point of view and that of the students’. The questionnaire contains 48 items. The QTI measurement tool can serve as a valuable source of information for teachers in comparing their self-assessment with the student’s view, which can obviously enhance their professional development.